2017
DOI: 10.1177/0300060517706284
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with multi-drug-resistant Acinetobacter baumannii nosocomial infections at a tertiary care hospital in Makkah, Saudi Arabia - a matched case–control study

Abstract: ObjectiveTo determine risk factors for multi-drug-resistant Acinetobacter baumannii (MDR-AB) nosocomial infections in intensive care units in a tertiary care hospital, Makkah, Saudi Arabia.MethodsWe performed a hospital-based, matched case–control study in patients who were admitted to Al Noor Specialist Hospital between 1 January 2012 and 31 August 2012. The study included cases of A. baumannii nosocomial infection and controls without infection. Controls were matched to cases by age and ward of admission.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Ballouz et al [26] indicated that a prolonged hospital admission is frequently associated with reduction of functionality, and increased exposure to steroids and antibiotics; and these factors seem to impact the mortality of A. baumannii bacteremia. A hospital-based, matched case–control study found that the risk factors associated with carbapenem resistant A. baumannii (CRAB) in nosocomial infections in ICU include immunosuppression, invasive procedures, central venous catheters, and an endotracheal intubation [7]. Gastrointestinal colonization by A. baumannii in ICU patients is a significant risk factor for spreading antimicrobial resistance, increases disease severity and provides an important reservoir for clinical infections and hospital outbreaks [27].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ballouz et al [26] indicated that a prolonged hospital admission is frequently associated with reduction of functionality, and increased exposure to steroids and antibiotics; and these factors seem to impact the mortality of A. baumannii bacteremia. A hospital-based, matched case–control study found that the risk factors associated with carbapenem resistant A. baumannii (CRAB) in nosocomial infections in ICU include immunosuppression, invasive procedures, central venous catheters, and an endotracheal intubation [7]. Gastrointestinal colonization by A. baumannii in ICU patients is a significant risk factor for spreading antimicrobial resistance, increases disease severity and provides an important reservoir for clinical infections and hospital outbreaks [27].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…The patterns of resistance and severity of A. baumannii infection depend upon the patient’s susceptibility to infection as a result of their underlying diseases [30, 31]. Patients with underlying illness such as DM, cancer, renal impairment and chronic pulmonary disorders have immune deficits that lead to increased susceptibility to infection caused by opportunistic pathogens [7, 9, 32]. However, individuals with such conditions tend to become at long-term hospitalization and under frequent invasive diagnostic and therapeutic interventions [33].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study conducted over 7 years form 2007 to 2014 at a large university hospital in Beirut showed that the a rate of XDR-AB colonization pressure was 315.4 cases/1000 ICU patient-days [ 3 ]. Another matched case–control study from a specialist hospital in the Kingdom of Saudi Arabia between January and August 2012, assessing potential risk factors for XDR-AB acquisition, showed that the proportion of ICU patients who harbored XDR-AB during their stay reached 33% (66/198 patients) [ 23 ]. These figures indicate in our geographical region that XDR-AB is rampant in critical care units.…”
Section: Discussionmentioning
confidence: 99%
“…In general, risk factors for XDR-AB acquisition may vary from one ICU to the other due to differences in applying standard precautions, compliance to hand hygiene, distance between beds, type of ICU whether open-bay or single-room [ 2 , 32 ]. On the other hand, risk factors including the use of invasive devices, treatment with broad-spectrum antibiotics, length of stay in ICU and contact pressure are commonly reported in several studies [ 2 , 3 , 23 , 33 ].…”
Section: Discussionmentioning
confidence: 99%